Supporting new firm's through Entrepreneurship education: a case of a successful course - Raposo, Mario (2019)
Entrepreneurship is a dominant force in contemporary economy. Entrepreneurship is a dynamic process of vision, change and creation. Entrepreneurship is a process of fundamental transformation, from an innovative idea, to the value proposal to the creation a new venture. It requires an application of energy and passion towards the creation and implementation of new ideas and creative solutions. The essential ingredients include: the willingness to assume risks, the ability to join a venture team, the creative skill to get necessary resources, ability to develop a solid business plan and the vision to recognize an opportunity. As entrepreneurship is about devising and implementing new ideas and practices, a strong educational foundation helps ensure that new ideas will be effective and substantive. This paper starting from the theoretical framework of entrepreneurship based on different lines of thought and with different approaches, will try to describe the dimensions of the Entrepreneurial education process and how this process promotes students' attitudes and intentions favorable to create business start-ups. In a practical way, will be presented the successful case of an course of entrepreneurship of technological base, that has been going on for some years in a partnership between several universities. Examples of successful startups, resulting from the course will be mentioned.